Back Cover: CH Activation Generates Period‐Shortening Molecules That Target Cryptochrome in the Mammalian Circadian Clock (Angew. Chem. Int. Ed. 24/2015). Issue 24 (8th June 2015) - Oshima, Tsuyoshi; Yamanaka, Iori; Kumar, Anupriya; Yamaguchi, Junichiro; Nishiwaki‐Ohkawa, Taeko; Muto, Kei; Kawamura, Rika; Hirota, Tsuyoshi; Yagita, Kazuhiro; Irle, Stephan; Kay, Steve A.; Yoshimura, Takashi; et al.
<x xml:space="preserve">Abstract</x> A focused library of KL001 derivatives, a period‐lengthening modulator of the mammalian circadian clock, was rapidly constructed by CH activation chemistry. In their Communication on page 7193 ff., S. Irle, T. Yoshimura, K. Itami et al. describe both new period‐lengthening molecules and the first period‐shortening molecules that target the cryptochrome. The picture (Haruko Hirukawa) illustrates the power of the CH activation catalyst in triggering opposite modes of action in small molecules.